AB1104 ANALYSIS OF ANTINUCLEAR ANTIBODY TITERS AND PATTERNS USING HEP 2 INDIRECT IMMUNOFLUORESCENCE IN VARIOUS LIVER DISEASES. (2nd June 2020) - Wei, Q.; Jiang, Y.; Yang, M.; Xie, J.; Xiao, M.; Gu, J.
Abstract : Background: Abnormal liver function can be seen in not only hepatitis B virus infection (HBV), hepatitis C virus infection (HCV), hepatic carcinoma (HCC), but also in primary biliary cirrhosis (PBC), autoimmune hepatitis (AIH), and systemic autoimmune rheumatic diseases (SARD). Antinuclear antibody (ANA) testing using indirect immunofluorescence assay (IIFA) is a common and economical method which contributes to detect SARD and autoimmune liver diseases [1]. Objectives: Our objective was to investigate ANA positivity, titers and their patterns in multiple liver diseases, including PBC, AIH, HBV, HCV, and HCC, compared to healthy controls (HC). Methods: 2537 patients with SARD, 137 PBC cases, 57 AIH cases, 3420 HBV cases, 769 HCV cases, 268 HCC cases, and 1073 HC were retrospectively assessed. The titers and patterns of ANA were detected with the IIFA method. Results: ANA positivity rate was considerably discernible between these diseases, which is 90.1% in SARD, 93.4% in PBC, 49.1% in AIH, 19.1% in HBV, 13.9% in HCV and 23.5% in HCC. Moreover, only 4.9% of HCC cases, 2.5% of HBV patients and 1.6% of HCV patients had an ANA titer ≥ 1:320. The mixed pattern which composed of at least two patterns majorly lied in PBC. AC-15 and AC-21 was frequently related to liver diseases; the former pattern was more frequently found in AIH (84.2%) and PBC (8.8%), and the latter pattern was easily seen in PBC (62.2%) and HCC (22.6%). The positive rate of ANA in HC was 12.2% and its major pattern was AC-2. Conclusion: There are differences in ANA positivity among patients with SARD and various liver diseases. Some mixed patterns may provide important evidence for the diagnosis of PBC. Clinicians should pay attention to ANA patterns and titer during the interpretation of this test. References: [1]Damoiseaux J, Andrade L, Carballo OG, Conrad K, Francescantonio P, Fritzler MJ, Garcia DLTI, Herold M, Klotz W, Cruvinel WM, Mimori T, von Muhlen C, Satoh M, Chan EK, (2019) Clinical relevance of HEp-2 indirect immunofluorescent patterns: the International Consensus on ANA patterns (ICAP) perspective. ANN RHEUM DIS 78: 879-889 Acknowledgments: None. Disclosure of Interests: None declared